Social Sharing of Emotions in Social Media System on the Example of Creepypasta on Reddit - Chornobylskyi, Anton; Kyrylova, Oksana; Krupskyi, Oleksandr; Khotiun, Liudmyla (Information & Media, 2023)
As part of this study, it was suggested that, like other social media, Reddit allows to embody models of communicative interaction in a digital environment. The comments under three creepypastas published on the subreddit NoSleep, were selected as the object of the study. To prove the original thesis, the comments were analyzed from the perspective of social sharing of emotions (SSE) — a process characteristic of real interpersonal communication. The comments were studied manually using the method of intentional analysis. As a result of the study, the main intentional categories characteristic of the social sharing of emotions in the comments on NoSleep were established. It was concluded that SSE in the comments under creepypastas generally coincides with the existing models, and the differences found can be explained by the specifics of the digital environment and the concrete features of Reddit as social media.
Keywords: user comments; social networking site; Reddit; social sharing of emotions; creepypasta